Plane electroelastic problem for a cracked piezoelectric half-space subject to remote electric field action - Khoroshev, K.G.; Glushchenko, Yu.A. (European journal of mechanics, A, Solids, 2020)
Plane electroelastic problem is considered for a longitudinal crack in a transversely-isotropic piezoelectric half-space subject to remote electric field perpendicular to the flat surface of the half-space. The flat surface is fully covered by thin electrode and free of mechanical load. The Lekhnitskii’ generalized complex potentials are used for the solution representation. For a case of an internal crack, boundary conditions on the flat surface are satisfied analytically by use of the Cauchy integration technique. The least-square method is applied for satisfying boundary conditions on the crack surface. An edge crack is considered. Numerical investigations are carried out for a internal or an edge crack in dependency on crack orientation and location. The results showed that one of the most dangerous crack is parallel to the flat surface. A crack perpendicular to the flat surface does not cause any significant electroelastic field in a piezoelectric half-space. Location of a crack relative the flat surface influences on electromechanical coupling near its tips. •A piezoelectric half-space with a crack is considered.•Remote electric field is supplied.•Boundary conditions on the crack surface are satisfied by the least-squares method.•The most dangerous crack is parallel to the flat surface of the half-space.